2020
DOI: 10.1021/acsami.0c15570
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Polymer Interfaces for Electrochemically Assisted Mercury Remediation

Abstract: Nanostructured polymer interfaces can play a key role in addressing urgent challenges in water purification and advanced separations. Conventional technologies for mercury remediation often necessitate large energetic inputs, produce significant secondary waste, or when electrochemical, lead to strong irreversibility. Here, we propose the reversible, electrochemical capture and release of mercury, by modulating interfacial mercury deposition through a sulfur-containing, semiconducting redox polymer. Electrodep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…It is worth noting that redox-promoted anodic stripping on polymer interfaces can enhance the regeneration efficiency. For example, the anodic stripping by redox-mediated oxidation has been shown to regenerate mercury-deposited polymer electrode (poly(3-hexylthiophene-2,5-diyl)-CNT [carbon nanotube] coated on titanium) with high reversibility (regeneration efficiency >85%) and fast regeneration kinetics (2.08 × 10 −2 s −1 for P3HT-CNT/titanium, compared with 1.70 × 10 −3 s −1 for bare titanium) for reversible mercury capture and release ( Candeago et al., 2020 ), and similar approaches could be employed for other critical metals too.…”
Section: Electrochemical Separations For Selective Recoverymentioning
confidence: 99%
“…It is worth noting that redox-promoted anodic stripping on polymer interfaces can enhance the regeneration efficiency. For example, the anodic stripping by redox-mediated oxidation has been shown to regenerate mercury-deposited polymer electrode (poly(3-hexylthiophene-2,5-diyl)-CNT [carbon nanotube] coated on titanium) with high reversibility (regeneration efficiency >85%) and fast regeneration kinetics (2.08 × 10 −2 s −1 for P3HT-CNT/titanium, compared with 1.70 × 10 −3 s −1 for bare titanium) for reversible mercury capture and release ( Candeago et al., 2020 ), and similar approaches could be employed for other critical metals too.…”
Section: Electrochemical Separations For Selective Recoverymentioning
confidence: 99%
“…Enhancing SeDER removal performance will require that agricultural drainage is concentrated by at least 1 order of magnitude (e.g., through capacitive deionization and electrosorption), while cell design will need to significantly enhance the mass transfer rate of Se oxyanions. Better electrode and cell designs (e.g., functionalized electrode interfaces) could also be coupled with a localized heating strategy to sustain an elevated cathode surface temperature for energy-efficient Se removal …”
Section: Resultsmentioning
confidence: 99%
“…45 For example, ILs have been reported to alter solvation of metal ions, influencing electrochemical deposition processes, 46−48 and polymeric additives have been found to act as moderators for metal deposition, as they are adsorbed on electrode surfaces. 49,50 Recent studies have also reported on surface functionalization of interfaces using conducting polymers to mediate electrochemical reactions of interest in other environmental applications, including water purification 51 and advanced electrochemical separations. 52 Thus, this study is focused on understanding the role of electrolytes based on NOHMs with an ionically tethered polyetheramine canopy (HPE) (NOHM-I-HPE) in the electrodeposition of Zn, with the objective of discerning any potential near-electrode surface effects of NOHMs.…”
Section: T H Imentioning
confidence: 99%
“…Although the study using Cu­(II) demonstrated potential opportunities for NOHMs as electrolyte additives, little is still known about the near-electrode surface behavior of NOHMs in electrolyte solutions and their effect on the electrodeposition of metal ions of interest (e.g., zinc (Zn)) in various electrochemical systems. Other complex electrolytes containing additives such as ILs and polymers have been found to have a nonideal behavior on electrode surfaces and impact metal deposition . For example, ILs have been reported to alter solvation of metal ions, influencing electrochemical deposition processes, and polymeric additives have been found to act as moderators for metal deposition, as they are adsorbed on electrode surfaces. , Recent studies have also reported on surface functionalization of interfaces using conducting polymers to mediate electrochemical reactions of interest in other environmental applications, including water purification and advanced electrochemical separations …”
Section: Introductionmentioning
confidence: 99%